Innate Lymphoid Cells are Present at Healthy Patients Spinal Enthesis, Providing a Potential Mechanism for Spondyloarthropathy Pathogenesis. Issue 1 (April 2016) - Cuthbert, Richard; Fragkakis, Evangelos M.; Giannoudis, Peter; Dunsmuir, Robert; Millner, Peter; McGonagle, Dennis
Background: The pathogenesis of murine spondyloarthropathy (SpA) has been intimately linked to the presence of Interleukin(IL)-23 responsive, innate like lymphocytes at different anatomical regions including spinal enthesis. Human SpAs are associated with Single nucleotide polymorphisms (SNPs) in genes related to the IL-23 pathway and drugs that block IL-12/23 have shown efficacy. We hypothesized that the normal human enthesis has a population of resident innate lymphoid cells (ILCs) that could be involved in governing entheseal immune homeostasis. In particularly entheseal resident type 3 ILCs (ILC3s) may be critical, since ILC3s in other tissues have been shown to produce inflammatory cytokines in response to IL-23. Methods: Normal spinal enthesis were harvested from healthy patients undergoing spinal surgery and enzymatically digested prior to fluorescence activated cell sorting (FACS). Cellular immunophenotyping and cell sorting was performed on enthesis samples harvested from 6 patients; ILC3s, were identified as lineage (CD3- TCRγδ- TCRαβ- CD19- CD14- CD11c- CD1a- CD303- FcεRI- CD34- CD123-) and cellular surface marker CRTH2 negative with positive expression of CD45, CD127, CD117. ILC2s, which have been linked to fibrotic reactions, were identified as lineage negative with positive expression of CD45, CD127 and CRTH2. The expression of RORγt transcript was tested in sorted populations by RTqPCR. Anterior cruciate ligament (femoral enthesis) was obtained from subjects with knee OA and injured enthesis undergoing repair were also collected and analyzed by immunohistochemistry (IHC). Results: All sorted samples contained ILC3s, median proportion 0.09% (range 0.015–0.63). Transcript analysis confirmed the expression of RORγt, transcript, an ILC3 related transcription factor, in sorted ILC3 populations, with ILC3s expressing 51-fold greater relative expression in comparison to unsorted digests. 5 of 6 sorted samples contained ILC2s, median proportion 0.20% (range 0–0.49). RORγt expression was detected in knee OA and there was widespread expression of RORγt in inflammatory infiltrates in injured enthesis as shown by IHC. Conclusions: Our findings show that ILCs are present in the normal human spinal enthesis and may be greatly increased in frequency following injury. These findings provide strong evidence of ILC presence in normal human enthesis and suggest a potential link between cellular dysregulation of the IL-23/17 axis and SpA pathology at sites of micro damage.